Representations and symbols of Kuafu's myth in Analytical Psychology and Chinese culture: History vs. contemporary, consciousness vs. unconscious, collective vs. individual. (September 2019) - Guo, Ruitong; Shen, Heyong; Zhang, Yancui; Wu, Bo
The paper collaboratively probes the diachronic, cultural and psychological resources inherited from the classical heroic myth of China, Kuafu Chases after the Sun . With the conceptual system of Analytical Psychology and Chinese culture, starting with ancient mythological texts, the authors carry out studies on three dimensions of the historical and contemporary images of Kuafu, the conscious and unconscious contents, and the collective and the individual psyche. First, the paper explores the collective representations of consciousness based on ancient and modern works of art, reviews and cultural phenomena. Second, on collective and cultural unconscious symbols, Kuafu is a heroic archetypal image, and there are four dynamic images from change to transformation. Third, the exploratory study of a case with Sandplay Therapy finds the projection and emergence of the Kuafu myth for individual consciousness is of great clinical value for helping the client experience and transform their psychological conflicts.